Penilaian Komponen Hasil dan Indeks Intercropping 22 Jagung Hibrida Pada Sistem Intercropping Jagung-Kedelai - Jajang Supriatna; Muhamad Sahrul Sidik; Rama Adi Pratama; Fakhri Nasharul Syihab; Yuyun Yuwariah; Dedi Ruswandi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to determine the performance of the yield components and the intercropping index of 22 hybrid maize in the maize-soybean intercropping system. This research was carried out in Cikajang, Garut Regency from January 2021 to June 2021. The method used in this research is a quantitative descriptive and experimental method. The experimental design used was a randomized block design with 27 treatments made in 3 replications. The genetic material used was 22 test hybrids from the Padjadjaran University collection and 5 commercial hybrids as comparisons. Assessment of yield components was carried out using The Least Significant Increase (LSI) test assessed for 4 yield components consisting of cob diameter, cob length, number of seeds cobs, and dry seed/plant weight. Intercropping index assessment was analyzed based on the calculation of Land Equivalent Ratio (LER), Area Time Equivalent Ratio (ATER), and Aggressivity (A). The results showed that there were 4 hybrids that had high yields in the maize-soybean intercropping system including DRc6 x DRc7, DRc8 X MDRc18.8.1, DRc8 X MDRc1.1.3 and MDRc3.1.4 X MDRc18.5.1. There are 3 profitable hybrids in the intercropping system of soybean maize based on the intercropping index including DRc4 X MDRc7.2.3, DRc8 x DRc9, and MDRc7.4.3 x MDRc18.8.1.